More to producing a thesis - New Straits Times, Michael Sun (2010)
Quality doctoral thesis begins with effective supervision. Universiti Putra Malaysia Faculty of Modern Languages and Communications senior Lecturer Dr Vijay Kumar Mallan believes research into doctoral education helps effectual doctoral supervision.